The Prevalence of High Grade Prostatic Intraepithelial Neoplasia in Prostatic Biopsies Diagnosed As benign Prostatic Hyperplasia at Muhimbili National Hospital, Dar es Salaam. (Tanzania Medical Journal, 2008)
Setting: The study was conducted at Muhimbili National Hospital in Dar es Salaam in the department of Histopathology and Morbid Anatomy.Study design: The study was a retrospective cohort type in which prostatic biopsy reports of patients with histological diagnosis of BPH were microscopically re-evaluated in order to reveal whether there was any presence or absence of HGPIN, which is a significant risk factor for the development of prostatic adenocarcinoma.Objective: To determine the prevalence of high-grade PIN in BPH as diagnosed at Muhimbili National Hospital and relate it to its histomorphological types as well as the ages of the patients and its distribution in different types of prostatic biopsies and also compare the distribution of HGPIN with that of adenocarcinoma in prostatic biopsies during the same period of study.Methodology: The data was retrieved from register books, histological reports and computer files. The data was used as a source of information in order to determine the number of PC and BPH histologically reported , types of prostatic biopsies, and age of the patients. H&E stained slides on which the diagnosis of PC or BPH was previously made were retrieved from archives and then microscopically reviewed for histological confirmation of the diagnosis. The slides with the diagnosis of BPH were further re-examined for the presence or absence of HGPIN. For those slides which were missing, their corresponding paraffin blocks were re-cut, stained with H&E and reported for the presence or absence of high-grade PIN.Results: Out of 687 specimens of prostatic biopsies received in 3 years (mean 229 per year), 321(46.7%) were diagnosed as adenocarcinoma and 366 (53.3%) were supposedly diagnosed as BPH. The mean age of patients with prostatic cancer (PC) was 75.6 years while that of BPH was 67 years. The number of patients with PC below 60 years was 23 (7.2%) and those with BPH was 46 (12.6%). However, 122 (38%) patients with PC were between 60-70 years of age while in those with BPH, 172 (47%) were in the same age range. Of the 366 patients who were diagnosed as having BPH, 163 (44.5%) were also found to have HGPIN. The mean age of patient with high-grade PIN in PBH was 69.6 years. In the 163 patients with HGPIN, 20(12.3%) were below 60 years of age , 83 (50.9%) were between 60-70 years and 60 (36.8%) were above 70 years. Of the 366 prostatic specimens in which the diagnosis of BPH was made, 238 (65%) were from needle biopsy (NB), 47 (12.9%) from transurethral resections of prostate (TURP) and 81(22.1%) were from open prostatectomy (OP). Similarly, out of 238 NB, 82 (34.5%) had HGPIN while in 47 TURP biopsies, 21 (44.7%) had HGPIN and in 81 RP specimens, 60 (74.1%) had HGPIN. With regard to morphological patterns of PIN, tufting was the most frequent in all types of biopsies followed in descend order by Cribriform, micropapilary, and flat.Conclusion: The study has conclusively shown that there is a high prevalence of HGPIN in prostatic biopsies diagnosed and reported solely as BPH at our hospital as has been suspected before. The age distribution of HGPIN has indicated that the lesion is an intermediate stage between BPH on one hand and PC on the other, further confirming that HGPIN is precursor or pre-invasive stage to invasive prostate carcinoma. The identification of increased number of HGPIN in biopsy specimens has an important implication for the management of the patient.Recommendations: Bearing in mind that HGPIN is strongly predictive of the presence of prostatic carcinoma, HGPIN should be included in pathology report. The finding of HGPIN in a patient should clinically be closely followed-up with serum PSA, digital rectal examination (DRE) and ultrasound, preferably trans rectal ultrasound or repeated needle biopsy for a defined period of time. Tanzania Medical Journal Vol. 23 (1) 2008: pp. 1-4